The Effectiveness of the CAKE Mobile Application in Improving English Speaking Skills - Syakila Nazla Muchari; Putri Kinaya Maharani; Arika Zainina Syasya; Husnul Khatimah; Sri Intan Ikhwandari Lubis; Juliana Juliana (Journal of English Language and Education, 2026)
The development of English-speaking skills is essential for students, particularly in today’s globalized world, where effective communication is crucial. Despite this, many students face challenges in achieving speaking proficiency, resulting in a gap between their current abilities and desired outcomes. This study evaluates the effectiveness of the CAKE mobile application, an interactive language learning app that focuses on improving speaking skills through real-time practice and feedback, in enhancing students' speaking skills through Classroom Action Research (CAR). Involving 20 junior high school students, the study employed both qualitative (observations) and quantitative (pre-test and post-test) data collection methods. Results indicated significant improvement in speaking performance, with the post-test mean score increasing from 73.50 in Cycle I to 85.10 in Cycle II. Additionally, the percentage of students meeting the minimum mastery criterion (KKM) rose from 25% to 85%. The findings suggest that integrating the CAKE mobile application into the curriculum serves as an effective tool for enhancing speaking proficiency.